HUBUNGAN KARBOHIDRAT PADA SUSU YANG DIKONSUMSI DENGAN KEJADIAN KARIES GIGI BOTOL PADA ANAK PLAY GROUP - Ni Nyoman Dewi Supariani; I Made Budi Artawa; I Nyoman Wirata (Jurnal Kesehatan Gigi (Dental Health Journal), 2013)
The Conntmption of Milk Formula using bottle can couse caries, because milk prodtrct contains of carbohydrate that is a medium that goodfor germs to produce acid. Tltis cortclitiort will watering clov'n the forming of plaque that is the cattse of teeth cliseuse or suicl as rutrsing bottle cories. This obsen,etion has a goal to know the relation between the contents in the milk that consumption with caries that happened around the child. The population of this observation are the students in Play Group Kuncup Mekar Denpasar that has 36 students. This observation ,r description with crossectional design. The collecting of the data using enquette. The analyze of this obsentation is using statistic univariat the are frequency, percentage, and analyzing multivariate with Pearson Test. The result show the freqltency of bottle caries are 54, the teeth that mostly caries is incisivus I right top that has sum 18 (33,3 %r) and thefewest is incisivus II left top that has sttm 9 (16,7 %"). Carbohydrate content at consumed milk many milk of Chilkid thct is 6l gram/ml, and at least milk of Nutrilon that is 2 gram/ml. caries bottle Frequency is most with llama gift/giving of milk 29 until 38 months, with bottle caries 35 ( 64,81%0), at least with long gift/ giving of milk nine until 18 months with bottle caries I ( 1,85%o). Frequency giuing of bottle milk one until thrice ane day with amount of bottle caries 47 ( 87,0%0). Pursuant to result of Statistical Test with test of Pearson scored a point by correlation is - 0,078 with probability 0,285 (bigger than at 0,05). This Research node there not corelation having a meaning of between carbohydrate content at consumed milk with occurence of bottle caries at child in Play Group Kuncup Mekar.